Redefining 3Dimensional placental membrane microarchitecture using multiphoton microscopy and optical clearing - Richardson, Lauren; Vargas, Gracie; Brown, Tyra; Ochoa, Lorenzo; Trivedi, Jayshil; Kacerovský, Marian; Lappas, Martha; Menon, Ramkumar (Placenta, 2017)
INTRODUCTION: Remodeling of human placental membranes (amniochorionic or fetalmembrane) throughout gestation, a necessity to accommodate increasing uterine volume, involves continuous alterations (replacement of cells and remodeling of extracellular matrix). Methodologic limitations have obscured microscopic determination of cellular and layer-level alterations. This study used a combination of advanced imaging by multiphoton autofluorescence microscopy (MPAM) and second harmonic generation (SHG) microscopy along with tissue optical clearing to characterize the 3Dimensional multilayer organization of placental membranes. METHODS: Placental membranes biopsies (6 mm) collected from term, not-in-labor cesarean deliveries (n = 7) were fixed in 10% formalin (native) or treated with 2,2'-thiodiethanol to render them transparent for deeper imaging. Native and cleared tissues were imaged using MPAM (cellular autofluorescence) and SHG (fibrillar collagen). Depth z-stacks captured the amnion epithelium, underlying matrix layers, and in the cleared biopsies, the decidua layer. RESULTS: MPAM and SHG revealed fetal membrane epithelial topography and collagen organization in multiple matrix layers. Term amnion layers showed epithelial shedding and gaps. Optical clearing provided full-depth imaging with improved visualization of collagen structure, mesenchymal cells in extracellular matrix layers, and decidua morphology. Layer thicknesses measured by imaging corroborated with histology. Mosaic tiling of MPAM/SHG image stacks allowed large area visualization of entire biopsies. CONCLUSION: MPAM-SHG microscopy allowed for study of this multi-layered tissue and revealed shedding, gap formation, and other structural changes. This approach could be used to study structural changes associated with membranes as well as other uterine tissues to better understand events in normal and abnormal parturition.
Keywords: mikroskopie fluorescenční multifotonová; histocytologické preparační techniky; Second Harmonic Generation Microscopy; Imaging, Three-Dimensional; Membrane rupture; Epithelial shedding; těhotenství; Second harmonic generation microscopy; Humans; Optical clearing; lidé; Extracellular Matrix; zobrazování trojrozměrné; mikroskopie generování druhé harmonické; Pregnancy and parturition; Female; extracelulární matrix; Multiphoton microscopy; Microscopy, Fluorescence, Multiphoton; ženské pohlaví; Placenta; placenta; Pregnancy; Histocytological Preparation Techniques; extraembryonální obaly; Nonlinear optical microscopy; Amniochorion; Extraembryonic Membranes